Privacy and Technology: Reconsidering a Crucial Public Policy Debate in the Post-September 11 Era. - Nelson, Lisa (Public Administration Review)
In the post September 11 era, one truism in the ongoing public policy debate surrounding technology and privacy is that there is no easy solution to the increasing presence of technology in our lives. There are, however, several long-standing guiding principles. We must be wary of extending political authority to protect privacy without careful contemplation of the consequences. While it may appear that the idea of balancing technology and privacy is novel, the tension between them is informed by a broader theoretical framework that is inherent to democracy. Understanding this broader theoretical framework is helpful in identifying ways to advance the debate toward policy solutions rather than continuing a dogmatic discussion that juxtaposes technological innovation with the loss of privacy. The purpose of this discussion is not to settle the public policy debate. Instead, the aim is to consider how long-standing constitutional doctrine and the theoretical framework of democracy can lend insight into the current debate surrounding privacy and technology. Reprinted by permission of the publisher.